2018
DOI: 10.1080/09581596.2018.1447647
|View full text |Cite
|
Sign up to set email alerts
|

Engaging religious leaders to support HIV prevention and care for gays, bisexual men, and other men who have sex with men in coastal Kenya

Abstract: In Kenyan communities, religious leaders are important gatekeepers in matters of health and public morality. In a context that is generally homophobic, religious leaders may aggravate or reduce stigmatization of sexual minorities such as gay and bisexual men, and other men who have sex with men (GBMSM). Literature indicates mixed results in efforts to encourage religious leaders to work effectively and sensitively with issues regarding HIV and sexuality. This paper describes the implementation of an engagement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 41 publications
3
18
0
Order By: Relevance
“…Religion maintained a connection to home communities and cultures; hence, participants noted that churches could be harnessed as a platform to share HIV information once religious leaders were trained. Prior work in Kenya documented that facilitated engagement of religious leaders contributed to supportive views of sexual health [32]. Medical mistrust emerged; in other contexts, medical mistrust among refugees has been linked with past and current experiences of being 'Most times we can't go for an outreach without a counsellor who we attach to an interpreter, because sometimes they trust that person who speaks their language who explains very well in their own language'.…”
Section: Discussionmentioning
confidence: 99%
“…Religion maintained a connection to home communities and cultures; hence, participants noted that churches could be harnessed as a platform to share HIV information once religious leaders were trained. Prior work in Kenya documented that facilitated engagement of religious leaders contributed to supportive views of sexual health [32]. Medical mistrust emerged; in other contexts, medical mistrust among refugees has been linked with past and current experiences of being 'Most times we can't go for an outreach without a counsellor who we attach to an interpreter, because sometimes they trust that person who speaks their language who explains very well in their own language'.…”
Section: Discussionmentioning
confidence: 99%
“…Religious leaders also showed that they were able to gradually apply more humanistic, caring discourse, indicating that one can interrupt the cycle of socialization and stand up for change. 43…”
Section: Structural Intervention Strategiesmentioning
confidence: 99%
“…This implies shared decision-making throughout projects and the greatest community empowerment [ 37 ]. It entails involving individuals with lived experience, members of the public, and/or organisations representing them as decision-makers not only when conducting data collection and analysis and disseminating findings but also when setting research projects’ topics and questions and shaping projects’ design [ 13 , 36 , 43 ]. In this paper, the terms ‘people with lived experience’ and ‘members of the public’ are primarily used rather than patient, community, or community member.…”
Section: Introductionmentioning
confidence: 99%